Creating a Secure Network: The 2001 Anthrax Attacks and the Transformation of Postal Security. (June 2014) - Ellis, Ryan
The 2001 anthrax attacks transformed the US postal network into a site of uncertainty and danger. Five individuals died as a result of anthrax exposure, while 22 individuals were infected; estimates place the cost of the attacks, including sanitation and lost revenue, at $6 billion. The attacks highlighted the limitations and particularities of pre-existing biological-defence efforts and led to the adoption of new practices of postal security. In this article I examine the failure of pre-attack planning and critically analyse the creation and implementation of new security standards within the postal network in the wake of the 2001 attacks. Through archival research conducted at the Smithsonian Institution and documents obtained under the Freedom of Information Act (FOIA), the article traces the politics inscribed within the architecture of new security technologies. The creation of new forms of security was a contentious and fraught process that brought together a cross-section of interest groups, including postal labour, large-volume mailers, and postal management. Ultimately, however, these new forms of security serve to reinforce, rather than disrupt, pre-existing structures of power. New security practices serve the interests of large-volume commercial mailers - long-entrenched and central players in postal politics -at the expense of postal workers and the general public. The article emphasizes the possibilities and limitations of disasters to create moments of disruption and under-gird new political interventions.